Geoprocessamento aplicado à análise da paisagem: transformações no prolongamento da Avenida João Paulo II, Ananindeua (PA) - PEREIRA, Carla Braga (2019)
The landscape transformations caused by the anthropic actions symbolize the temporal and spatial dynamism of society, such as the urban landscape, which occurs in local scale. In this regard, the urban landscape may express, processes, functions, values, several shapes and multiple actions, such as a road construction. Based on this principle, the present study aims to analyze the landscape transformations that occur with the extension of João Paulo II avenue, in the Ananindeua City. Para State, Brazil) under the political, economic, environmental and social aspects. Geoprocessing techniques coupled with local social reports were used in this work. The mapping of the temporal and spatial landscape transformations was performed from field data and orbital images downloaded from Google Earth, from 2013 to 2018, which corresponds to the beginning and end of avenue construction. Thus, relevant information on physical-environmental, social changes and use and coverage land, were collected, such as population removal, extinction of streets and balnearies, environmental impacts (noise and water pollution and vegetal suppression) and increase in traffic accidents, etc. The new landscape brings elements from the past and present, resulting in an appreciation of the area based on the offering of environmental amenity, related to the Utinga Park, and the neighborhood access from a high-speed road by the João Paulo II avenue, in the revitalized stretch. We expect, for the next few years, a broad process of replacing low-income populations and the typical peripheral landscape with forms such as clubs and condominiums of medium and high status, which will reconfigure the Guanabara Neighborhood and surrounding areas.